Variation in Lipoprotein Level in Patients with Liver Cirrhosis Caused by Hepatitis B & C Viruses - Habibuilah Shaikh, Yasmin Shaikh, Noreen /rum, Ghultam Mustafa Dahri (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the effect ofcirrhosis on lipoprotein (a) level in patients ofhepatitis B & C. Place & Duration: This case control study conducted at the Biochemistry department, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Center Karachi. A total of 60 study subjects were enrolled in the study. Methods: Forty hepatitis B and C virus infection positive patients, after confirmation by ELISA method, with cirrhosis were included as cases and 20 normal subjects as control group from general population of similar age and of both sexes were also enrolled in the study. Estimation of serum lipoprotein (a) was done by ELISA method. prothrombin time by one stage method and liver enzymes by enzymatic method. Data analysis including paired and correlation analysis were compared using SASS software. P value upto 0.05 was considered significant for all comparison. Results: The lipoprotein (a) mean values were found statistically significantly diminished in both hepatitis B & C groups, which indicate decreased synthesis by the damaged liver. It showed statistically significant negative correlation with prothrombin time, AST and ALT in both patients groups. The results of our study indicate that there is an apparent decline in lipoprotein (a) level in hepatitis C patients ofcirrhosis as compared to other group ofhepatitis B. Conclusion: The remarkable decline and evidence of more decrease in the level of lipoprotein (a) in hepatitis C patients and its significant correlation with other biochemical parameters, reflects that the of serum lipoprotein (a) level evaluation may contribute, among other markers, to distinguish between causative organism of cirrhosis.